Occurrence of selected pharmaceuticals in water and sedimentof Umgeni River, KwaZulu-Natal, South Africa - Matongo, Solomon; Birungi, Grace; Moodley, Brenda; Ndungu, Patrick (Environ Sci Pollut Res, 2015)
Selected pharmaceuticals including antibiotics, an-tipyretics, a stimulant, an antiepileptic and an antipsychoticdrug were determined in wastewater, surface water and sedi-ment along the Umgeni River which is the main source ofwater to Durban City in KwaZulu-Natal, South Africa.Samples were analysed using high-performance liquid chro-matography coupled to a mass spectrometer (HPLC-MS/MS)after clean up and pre-concentration by solid phase extraction(SPE). At the wastewater treatment plant outlet, the antipyreticibuprofen was detected in concentrations up to 12.94μg/Land 15.96 ng/g in wastewater and bio-solids, respectively.The antipsychotic clozapine was detected in concentrationsup to 14.43μg/L and 18.75 ng/g in wastewater and bio-solids,respectively. Other pharmaceuticals namely sulfamethazine,sulfamethoxazole, erythromycin, metronidazole, trimetho-prim, acetaminophen, caffeine and carbamazepine were alsodetected but in lower concentration compared to clozapineand ibuprofen (<10μg/L or 10 ng/g). Clozapine and ibuprofenwere detected at high concentrations in the surface water andsediment of Umgeni River. The highest concentration of clo-zapine (78.33μg/L) was detected at the business park, whilethat for ibuprofen (62.0μg/L) was detected at the point where a tributary, Msunduzi, joins Umgeni. Metronidazole was onlydetected in sediment, and caffeine (2243.52 ng/g) was detect-ed at the highest concentration in the sediment at the bluelagoon sampling site. The antibiotic sulfamethoxazole wasalso detected in appreciable amounts up to 507.34 ng/g inthe sediment at the Msunduzi tributary sampling site. The datacollected implies that while insufficiently treated wastewatercontributes to surface water contamination, human activitiesalso contribute appreciably to the pharmaceutical loading ofRiver Umgeni
Keywords: Pharmaceuticals; Surface water; Sediment; Wastewater; Umgeni River